Students’ perceptions of emergency remote teaching in a writing course during COVID-19 - Guskaroska, Agata; Dux Speltz, Emily; Zawadzki, Zoë; Kurt, Şebnem (Frontiers in Education, 2022)
The COVID-19 pandemic forced most educational institutions in the US to quickly transfer to emergency remote teaching, finding many instructors and students unprepared. This study explored university students’ perspectives in a composition course during the emergency period and proposes guidance on designing a “student-friendly” online learning environment. This study examines the students’ concerns about and challenges with emergency remote teaching, the course’s benefits during the online learning period, and students’ recommendations for improvement. The research was conducted in seven sections of a multimodal composition course at a large, Midwestern university. Participants responded to a virtual discussion board at the beginning of online instruction and a survey after online instruction. Qualitative analysis of responses—guided by the Community of Inquiry (CoI) framework—showed that the participants expressed challenges with staying motivated, completing coursework, and feeling socially disconnected from instructors and classmates. Benefits expressed by the participants included increased flexibility in their schedules, improved time management skills, and increased virtual communication with instructors. This study highlights suggestions that can guide the design of composition courses and pedagogical practices for emergency remote teaching in the future.